Multimodal approaches for targeted treatment of heart failure - Akın, Ibrahim; Hamdani, Nazha; El-Battrawy, Ibrahim (European heart journal, 2025)
This commentary refers to ‘Therapy duration and improvement of ventricular function in de novo heart failure: the Heart Failure Optimization study’, by C. Veltmann et al., https://doi.org/10.1093/eurheartj/ehae334 and the discussion piece ‘Management of de novo heart failure with reduced ejection fraction: guideline-recommended medical therapy comes first’, by C. Veltmann et al., https://doi.org/10.1093/eurheartj/ehaf157.The article by Veltmann et al.,1 published in the European Heart Journal, discussing therapy duration and improvement of ventricular function in patients with de novo heart failure, has garnered significant interest among our research group. The paper emphasizes the role of the wearable cardioverter defibrillator (WCD) in conjunction with the initiation and achievement of targeted heart failure drug therapy. While the data presented are robust, several key points merit further discussion.